Treatment Characteristics of Kidney Stone Disease in Children - Anastasia V. Bairashevskaia; Sergei P. Baidin; Dmitry G. Tsarichenko; Vladimir S. Saenko (Вопросы современной педиатрии)
Kidney stone disease (KSD) is a disease caused by the formation of calculi in kidneys and other parts of the urinary tract. The rate of hospitalization of children with KSD worldwide is increasing. The adequate method of calculus extraction and further therapy according to calculus composition and metabolic disorders are crucial for effective treatment of patients with KSD and recurrence risk reduction. This review covers surgical (extracorporeal lithotripsy, percutaneous nephrolithotripsy, retrograde intrarenal surgery, ureterolithotripsy, laparoscopy, open surgery) and non-surgical (lithokinetic and litholytic) therapy. Special attention is paid to metaphylaxis, or recurrence prevention, and calculi formation. It is noted that medication of children with KSD can be aggravated by various adverse reactions, complexity in drugs dosages in children of first years of life. Moreover, all surgical methods are characterized by high risk of postoperative complications development. The relevance of KSD genetic nature in children, the role of lifestyle changes in disease development, the implementation of new drugs for metabolic disorders correction are presented in the article.